Relationship Among Adherence to the Mediterranean Diet and Anthropometric and Metabolic Parameters in Subjects with Obesity - Lampignano, Luisa; Zupo, Roberta; Donghia, Rossella; Guerra, Vito; Castellana, Fabio; Murro, Isanna; Di Noia, Carmen; Sardone, Rodolfo; Giannelli, Gianluigi; Triggiani, Vincenzo; De Pergola, Giovanni (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: There is moderate-to-high evidence that the Mediterranean diet prevents increases in body weight and waist circumference in non-obese individuals, but less is known about its effects in overweight and obese subjects. The present study was focused on exploring the cross-sectional association among the adherence to a Mediterranean diet and the most commonly used variables of metabolic and cardiovascular risk factors in a cohort of overweight subjects from a typical Mediterranean region, Apulia, in Southern Italy. Methods: The study was performed in a cohort of 1214 individuals, all overweight or obese but with no other clinical condition. We investigated the association with adherence to a Mediterranean diet, assessed using the PREDIMED score, and anthropometric parameters [namely body mass index (BMI), WC, waist to height ratio (WHtR) and neck circumference (NC)], fasting serum levels of glucose, insulin, uric acid and lipids (triglycerides, total cholesterol, HDL cholesterol, and LDL cholesterol), and blood pressure and insulin resistance, measured by HOMA-IR. Results: The waist to height ratio was negatively associated with a PREDIMED score ≥7 (p<0.04), whereas HDL cholesterol was positively associated with a PREDIMED score ≥7 (p<0.04). Conclusion: This study suggests that body fat distribution and HDL-cholesterol are the parameters most strongly influenced by MedDiet in Apulian subjects.
Keywords: HDL cholesterol